2006
DOI: 10.1021/cg050388f
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Planar and Chair-Shaped Cyclic Water Hexamers in a Unique Cyclohexanehexacarboxylate-Bridged Metal−Organic Framework

Abstract: The hydrothermal reaction of CoCl 2 ‚6H 2 O with cis, cis,cis,cis,cis-1,2,3,4,5,6-cyclohexane-hexacarboxylic acid (L) generates a unique three-dimensional metal-organic framework (MOF) of [Co 3 (L-6H)(H 2 O) 6 ] n (1). X-ray crystallography reveals that each L-6H ligand changes its conformation to a trans,trans,trans,trans,trans form to connect nine Co(II) atoms, and each Co(II) atom is connected to three L-6H ligands, leading to a MOF structure with high symmetry of R3 h. The coexistence of planar and chair-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 109 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…(H 2 O) 6 (chhc)] n [23]. We found that in the presence of 1,10-phenanthroline hydrothermal reactions of CoCl 2 · 6H 2 O, H 6 chhc and NaOH in an aqueous solution in the molar ratio of 1.0 : 1.0 : 0.…”
Section: Synthesesmentioning
confidence: 86%
See 1 more Smart Citation
“…(H 2 O) 6 (chhc)] n [23]. We found that in the presence of 1,10-phenanthroline hydrothermal reactions of CoCl 2 · 6H 2 O, H 6 chhc and NaOH in an aqueous solution in the molar ratio of 1.0 : 1.0 : 0.…”
Section: Synthesesmentioning
confidence: 86%
“…As illustrated in Fig. 2, the H 2 chhc 4− anions assume an e,e,e,e,e,e-conformation with the central ring adopting a chair-shaped conformation, the carboxylate and carboxyl groups being located at the equatorical sites, suggesting that the conformation of the ligand was changed from all-cis in the starting reagent into all-trans under the hydrothermal condition [23]. This configuration of the di-protonated cyclohexane- 1,2,3,4,5,6-hexacarboxylate anions is identical to that observed in Ni 2 (phen) 2 (H 2 chhc) [24].…”
Section: Description Of the Crystal Structurementioning
confidence: 99%
“…If one neglects the cyclohexane rings from the viewpoint of a magnetic superexchange pathway, each metal atom is connected by four syn-anti 2 -carboxylate bridges to form a 3-D tetrahedrally connected metal carboxylate inorganic network. The magnetic susceptibility indicated a weak antiferromagnetic coupling between the Mn(II) S = 5/2 spins [75], a relatively weak antiferromagnetic coupling between the Fe(II) S = 2 spins [75] and a significant antiferromagnetic coupling between the Co(II) S = 3/2 spins [74], respectively through the syn-anti carboxylate bridges. The nickel analogue, however, exhibits ferromagnetic exchange through the only effective magnetic exchange pathway of syn-anti carboxylate groups present within the 3D net [75].…”
Section: Coordination Compounds Based On 1245-cyclohexanetetracarbmentioning
confidence: 99%
“…The all-trans form II(e,e,e,e,e,e) is primarily observed in a series of 3D metal coordination frameworks [M 3 ( 9 -123456-CHA II )(H 2 O) 6 ] (M = Mn, Fe, Co and Ni) crystallized in high symmetry of R-3 [74][75]. The 123456-CHA II ligand lying across a three-fold axis connects nine octahedral metal atoms in a syn-anti pattern (Fig.…”
Section: Coordination Compounds Based On 1245-cyclohexanetetracarbmentioning
confidence: 99%
“…[13][14][15][16] The three neighboring carboxyl groups are suitable to construct metal-oxygen clusters, and also can rotate to satisfy the space requirement to bind metal centers in different directions to generate various complexes with interesting magnetic and spectroscopic properties. [17][18][19][20][21] As our continuous investigation on the coordination chemistry of multicarboxylate ligands, [22][23][24][25][26] we report herein two new layered nickel(II) coordination frame- …”
Section: Introductionmentioning
confidence: 99%